Meningkatkan Daya Saing Sekolah Swasta Berbasis Pesantren di daerah Dengan Menggunakan knowledge Management - qoyyimah, uswatun (Prosiding Seminas, 2011)
ABSTRAK Sekolah swasta berbasis pesantren di daerah mempunyai permsalahan yang berkaitan dengan sumber daya manusia antara lain masalah geografis, keluar masuknya staf, tambahan tugas admistrasi dan minimnya fasilitas. Dalam banyak kasus permaslahan ini menghambat sekolah sekolah tersebut dapat berkompetisi dengan sekolah negeri dan sekolah yang berada di kota besar. Tulisan ini menjelaskan tentang praktek knowledge managemen yang dapat dilakukan oleh sekolah sekolah ini agar mampu bersaing di daerah. Fokus dari tulisan ini antara knowledge acquisition, knowledge retention dan knowledge sharing. Kata kuci:sekolah, pesantren,knowledge management ABSTRACT Teachers and principals of Islamic private schools in rural areas have challenges in terms of adjusting to live in geographically remote areas, teachers turnover, increased administrative responsibilities and lack of facilities. The problems have made the schools in are left behind state schools and their counterparts in the cities. This paper attempts to uncover the knowledge management practice that can be implemented at Islamic private schools in rural areas to encounter the aforementioned problem as it is believed to enable organization to competitive advantage. This mainly focuses on what leaders must do to apply knowledge acquisition, knowledge retention and knowledge sharing. With knowledge management the problems related to knowledge lost can also be solved. Keywords:school, pesantren,knowledge management